Septic hip dislocation with a preserved femoral head: successful outcome following open reduction - Muhammad Kamal Muhammad Abdul Jamil,; Abdul Halim Abd Rashid,; Sharaf Ibrahim, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Septic arthritis of the hip in children represents a serious disorder with unfavourable long-term sequelae. In neonates, a poor hip outcome is expected especially if the treatment was delayed. Late sequelae can lead to structural joint damage and instability, causing deformity and dislocations which ultimately may result in limb length discrepancy, early degenerative changes and limited range of motion. Surgery at the appropriate time can improve the hip condition and functional outcome. Previous classifications of post septic hip sequelae are useful guides for treatment, but did not discuss one particular group of patient. This group-septic hip dislocation with a preserved femoral head, has recently been described as a distinct entity. This report highlights an 11-year follow-up of a 2-year-old child who had a successful outcome following open reduction and varus derotation osteotomy for a septic hip dislocation with a preserved femoral head.